Investigation of Friction Stir-Welded B4C Particles-Reinforced Copper Joint: Mechanical, Fatigue, and Metallurgical Properties - M. Vetrivel Sezhian; G. Chakravarthi; K. Giridharan; Balasubramaniam Stalin; B. Yokesh Kumar; P. Sureshkumar; J. Vairamuthu; Ramaswamy Krishnaraj (Advances in Materials Science and Engineering)
Solid-state friction stir welding (FSW) is a sophisticated technique that can join materials that are similar and different without significantly affecting the properties of the base materials. The purpose of this study is to enhance the tensile strength, micro-hardness, and fatigue strength of the copper (C1100) butt-joints reinforced with B4C nanoparticles. The effects of B4C nanoparticle inclusion on the mechanical properties of the fabricated joints are studied in correlation with the microstructural features of the welded joints using optical microscopy. The joints are fabricated on a specialized friction stir welding machine (VMC-TC-1200) with a square pin-profiled tool. Defect-free joints of 3 mm copper plates are produced at the constant tool rotational speed of 1100 rpm, welding speed of 30 mm/min, plunge depth of 0.25 mm, and constant axial stress of 5 kN. B4C particles of 1, 2, 3, and 4wt% are added to the joints and their properties are compared with the joints produced without the inclusion of B4C particles to study the effects of the addition of nanoparticles. The joints attained a maximum micro-hardness of 123 HV, fatigue strength of 159 MPa, and tensile strength of 203 MPa with the addition of 3% B4C. Microstructural investigations performed through an optical microscope and scanning electron microscope (SEM) indicated the presence of homogeneously distributed B4C particles engulfed by finely refined grains. The thermal conductivity of the B4C particles facilitated the smooth flow of copper around the particles by forming a thin lubricating layer, thus improving the properties of the joints. Furthermore, this study has established that the addition of B4C particles is an effective and eco-friendly method of producing strong joints which could be used for industrial and defense applications.